Perlindungan Represif dalam Awig-Awig di Bali pada Penyelesaian Sengketa Adat - Yulianingsih, Wiwin (Universitas Ekasakti, 2024)
The aim of this research is to explore the concept of repressive protection for customary disputes in Indonesia and explore the manifestation of repressive protection for Awig-Awig in Bali in resolving customary disputes. This research method is normative juridical, with a statutory, conceptual legal and legal case approach. Data comes from secondary sources, including primary legal materials, secondary legal materials and tertiary legal materials. Data analysis is descriptive analytical. The results of the research found that the concept of repressive protection for customary disputes in Indonesia is in the form of protecting indigenous peoples by enforcing the law as well as imposing sanctions on law violators. The legal certainty is as stated in the Constitution of the Republic of Indonesia of 1945 and Law of the Republic of Indonesia Number 6 of 2014 concerning Villages. The embodiment of this protection in Awig-Awig is as an example in Bali, where there are regulations regarding the rights of indigenous peoples as well as their application when disputes occur. Those who violate will be subject to sanctions.